WAYS TO FIGHT AGAINST COMPUTER CRIME - Haydarov Elshod Dilshod ugli (Galaxy International Interdisciplinary Research Journal, 2024)
Combating cybercrime requires a comprehensive approach. Given that technical measures alone cannot prevent crime, law enforcement agencies need to improve the effective investigation and punishment of cybercrime. In this thesis, comprehensive approaches to combating cybercrime are presented.